Secondary Typing of Mycobacterium tuberculosis Isolates with Matching IS6110 Fingerprints from Different Geographic Regions of the United States - Yang, Z. H. (American Society for Microbiology, 2001)
Fifty-nine isolates of Mycobacterium tuberculosis obtained from different states in the United States and representing 25 interstate clusters were investigated. These clusters were identified by computer-assisted analysis of DNA fingerprints submitted during 1996 and 1997 by different laboratories participating in the CDC National Genotyping and Surveillance Network. Isolates were fingerprinted with the IS6110 right-hand probe (IS6110-3′), the IS6110 left-hand probe (IS6110-5′), and the probe pTBN12, containing the polymorphic GC-rich sequence (PGRS). Spoligotyping based on the polymorphism in the 36-bp direct-repeat locus was also performed. As a control, 43 M. tuberculosis isolates in 17 clusters obtained from patients in Arkansas during the study period were analyzed. Of the 25 interstate clusters, 19 were confirmed as correctly clustered when all the isolates were analyzed on the same gel using the IS6110-3′ probe. Of the 19 true IS6110-3′ clusters, 10 (53%) were subdivided by one or more secondary typing methods. Clustering of the control group was virtually identical by all methods. Of the three different secondary typing methods, spoligotyping was the least discriminating. IS6110-5′ fingerprinting was as discriminating as PGRS fingerprinting. The data indicate that the IS6110-5′ probe not only is a useful secondary typing method but also probably would prove to be a more useful primary typing method for a genotyping network which involves isolates from different geographic regions.